Exploration of gender dynamics in the production and marketing of forage technologies in Kenya - Njiru, Nelly; Galiè, Alessandra; Wanyoike, Francis; Tawanda, Mashonganyika; Boonabaana, Brenda; Bisikwa, Jenipher; Njuguna-Mungai, Esther; Jones, Chris S.; Baltenweck, Isabelle (Frontiers in Animal Science, 2023)
Inadequate and poor-quality feed resources are a key constraining factor to livestock production, which compromises the livelihoods of many women and men dependent on livestock in most low- and middle-income countries (LMICs). Several forage varieties have been developed targeting smallholder farmers in developing countries, yet their adoption remains low, particularly among women farmers. Adoption of varieties could enhance livelihoods by increasing livestock productivity and also by providing an income from the sale of surplus forage. However, evidence on gendered barriers and incentives to adopt forage varieties is scarce. This study explores the gender dynamics influencing the uptake and commercialization of forage variety, Brachiaria grass (Urochloa), among women and men farmers in four subcounties in Kenya. Through a mixed-method approach, 260 individuals (59 women and 201 men) belonging to a household where at least one individual is a member of a dairy cooperative were interviewed. Complementary data from qualitative interviews engaging 16 single-sex focus group discussions (FGDs) and 8 key informant interviews (KIIs) was collected. Results reveal that Brachiaria grass is accessible to both women and men. Dairy cooperatives are important means for women and men to access extension services, useful information, and planting materials, but only a few women are cooperative members. Men face constraints of small land size rather than ownership and access hindrances that constrain women. These challenges privilege men as de facto owners of resources while subordinating women and disenfranchising them in terms of adopting this technology. Complex yet important pathways for women’s and men’s empowerment exist through the sale of planting materials, hay bales, and increased milk obtained when cows are fed with Brachiaria. We conclude that cooperative membership for men should be supported, at the same time challenging gender norms, that reduces women’s engagement with cooperatives, and their access to and control over land.